Panics and Principles: A History of Drug Education Policy in New South Wales 1965-1999 - Awan, F.T. (British journal of haematology, 2008)
When the problem of young people using illegal drugs for recreation emerged in New South Wales in the 1960s drug education was promoted by governments and experts as a humane alternative to policing. It developed during the 1970s and 1980s as the main hope for preventing drug problems amongst young people in the future. By the 1990s drug policy experts, like their temperance forbears, had become disillusioned with drug education, turning to legislative action for the prevention of alcohol and other drug problems. However, politicians and the community still believed that education was the best solution. Education Departments, reluctant to expose schools to public controversy, met minimal requirements. This thesis examines the ideas about drugs, education and youth that influenced the construction and implementation of policies about drug education in New South Wales between 1965 and 1999. It also explores the processes that resulted in the defining of drug problems and beliefs about solutions, identifying their contribution to policy and the way in which this policy was implemented. The thesis argues that the development of drug education over the last fifty years has been marked by three main cycles of moral panic about youth drug use. It finds that each panic was triggered by the discovery of the use of a new illegal substance by a youth subculture. Panics continued, however, because of the tension between two competing notions of young people’s drug use. In the traditional dominant view ‘drug’ meant illegal drugs, young people’s recreational drug use was considered to be qualitatively different to that of adults, and illegal drugs were the most serious and concerning problem. In the newer alternative ‘public health’ view which began developing in the 1960s, illicit drug use was constructed as part of normal experimentation, alcohol, tobacco and prescribed medicines were all drugs, and those who developed problems with their use were sick, not bad. These public health principles were formulated in policy documents on many occasions. The cycles of drug panic were often an expression of anxiety about the new approach and they had the effect of reasserting the dominant view. The thesis also finds that the most significant difference between the two discourses lies in the way that alcohol is defined, either as a relatively harmless beverage or as a drug that is a major cause of harm. Public health experts have concluded that alcohol poses a much greater threat to the health and safety of young people than illegal drugs. However, parents, many politicians and members of the general community have believed for the last fifty years that alcohol is relatively safe. Successive governments have been influenced by the economic power of the alcohol industry to support the latter view. Thus the role of alcohol and its importance to the economy in Australian society is a significant hindrance in reconciling opposing views of the drug problem and developing effective drug education. The thesis concludes that well justified drug education programs have not been implemented fully because the rational approaches to drug education developed by experts have not been supported by the dominant discourse about the drug problem. Politicians have used drug education as a populist strategy to placate fear but the actual programs that have been developed attempt to inform young people and the community about the harms and benefits of all drugs. When young people take up the use of a new mood altering drug, the rational approach developed by public health experts provokes intense anxiety in the community and the idea that legal substances such as alcohol, tobacco and prescribed drugs can cause serious harm to young people is rejected in favour of an approach that emphasizes the danger of illegal drug use